Building web apps with Angular and Typescript (O'Reilly, 2017)
"This course gets you started with web app development using Angular and TypeScript. You'll learn the basics of the Angular framework and its tooling for developing single page web apps; you'll generate a new project using Angular CLI and work with modules, components, dependency injection, routing, reactive programming, and inter-component communication; and then learn how to make HTTP requests to a web server. You'll finish up by doing a code review of a frontend sample online auction. The course works best if you've completed the O'Reilly videos "TypeScript Essentials" and "RxJS Essentials." Requirements include basic experience with JavaScript and understanding of an object-oriented programming language. Please have a current version of Node.js, the Chrome browser, and Visual Studio Code loaded on your computer before you start the class."--Resource description page